Respuestas
Respuesta dada por:
3
Debemos desaparecer la indeterminación.
![$\frac{\sqrt{9+h}-3}{h}=\frac{(\sqrt{9+h}-3)(\sqrt{9+h}+3)}{h(\sqrt{9+h}+3)}=\frac{h}{h(\sqrt{9+h}+3)}$ $\frac{\sqrt{9+h}-3}{h}=\frac{(\sqrt{9+h}-3)(\sqrt{9+h}+3)}{h(\sqrt{9+h}+3)}=\frac{h}{h(\sqrt{9+h}+3)}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B%5Csqrt%7B9%2Bh%7D-3%7D%7Bh%7D%3D%5Cfrac%7B%28%5Csqrt%7B9%2Bh%7D-3%29%28%5Csqrt%7B9%2Bh%7D%2B3%29%7D%7Bh%28%5Csqrt%7B9%2Bh%7D%2B3%29%7D%3D%5Cfrac%7Bh%7D%7Bh%28%5Csqrt%7B9%2Bh%7D%2B3%29%7D%24)
![$\frac{\sqrt{9+h}-3}{h}=\frac{1}{\sqrt{9+h}+3}$ $\frac{\sqrt{9+h}-3}{h}=\frac{1}{\sqrt{9+h}+3}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B%5Csqrt%7B9%2Bh%7D-3%7D%7Bh%7D%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B9%2Bh%7D%2B3%7D%24)
Entonces calculemos el límite
![$\lim\limits_{h\to 0}\left(\frac{1}{\sqrt{9+h}+3}\right)=\frac{1}{6}$ $\lim\limits_{h\to 0}\left(\frac{1}{\sqrt{9+h}+3}\right)=\frac{1}{6}$](https://tex.z-dn.net/?f=%24%5Clim%5Climits_%7Bh%5Cto+0%7D%5Cleft%28%5Cfrac%7B1%7D%7B%5Csqrt%7B9%2Bh%7D%2B3%7D%5Cright%29%3D%5Cfrac%7B1%7D%7B6%7D%24)
______________________________________________________________
![$\frac{\sqrt{x-b}-\sqrt{a-b}}{(x-a)(x+a)}=\frac{(\sqrt{x-b}-\sqrt{a-b})(\sqrt{x-b}+\sqrt{a-b})}{(x-a)(x+a)(\sqrt{x-b}+\sqrt{a-b})} $\frac{\sqrt{x-b}-\sqrt{a-b}}{(x-a)(x+a)}=\frac{(\sqrt{x-b}-\sqrt{a-b})(\sqrt{x-b}+\sqrt{a-b})}{(x-a)(x+a)(\sqrt{x-b}+\sqrt{a-b})}](https://tex.z-dn.net/?f=%24%5Cfrac%7B%5Csqrt%7Bx-b%7D-%5Csqrt%7Ba-b%7D%7D%7B%28x-a%29%28x%2Ba%29%7D%3D%5Cfrac%7B%28%5Csqrt%7Bx-b%7D-%5Csqrt%7Ba-b%7D%29%28%5Csqrt%7Bx-b%7D%2B%5Csqrt%7Ba-b%7D%29%7D%7B%28x-a%29%28x%2Ba%29%28%5Csqrt%7Bx-b%7D%2B%5Csqrt%7Ba-b%7D%29%7D)
![$\frac{\sqrt{x-b}-\sqrt{a-b}}{(x-a)(x+a)}=\frac{x-a}{(x-a)(x+a)(\sqrt{x-b}+\sqrt{a-b})}$ $\frac{\sqrt{x-b}-\sqrt{a-b}}{(x-a)(x+a)}=\frac{x-a}{(x-a)(x+a)(\sqrt{x-b}+\sqrt{a-b})}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B%5Csqrt%7Bx-b%7D-%5Csqrt%7Ba-b%7D%7D%7B%28x-a%29%28x%2Ba%29%7D%3D%5Cfrac%7Bx-a%7D%7B%28x-a%29%28x%2Ba%29%28%5Csqrt%7Bx-b%7D%2B%5Csqrt%7Ba-b%7D%29%7D%24)
![$\frac{\sqrt{x-b}-\sqrt{a-b}}{(x-a)(x+a)}=\frac{1}{(x+a)(\sqrt{x-b}+\sqrt{a-b})}$ $\frac{\sqrt{x-b}-\sqrt{a-b}}{(x-a)(x+a)}=\frac{1}{(x+a)(\sqrt{x-b}+\sqrt{a-b})}$](https://tex.z-dn.net/?f=%24%5Cfrac%7B%5Csqrt%7Bx-b%7D-%5Csqrt%7Ba-b%7D%7D%7B%28x-a%29%28x%2Ba%29%7D%3D%5Cfrac%7B1%7D%7B%28x%2Ba%29%28%5Csqrt%7Bx-b%7D%2B%5Csqrt%7Ba-b%7D%29%7D%24)
Llevamos al límite
![$\lim\limits_{x\to a}\frac{1}{(x+a)(\sqrt{x-b}+\sqrt{a-b})}=\frac{1}{4a\sqrt{a-b}}$ $\lim\limits_{x\to a}\frac{1}{(x+a)(\sqrt{x-b}+\sqrt{a-b})}=\frac{1}{4a\sqrt{a-b}}$](https://tex.z-dn.net/?f=%24%5Clim%5Climits_%7Bx%5Cto+a%7D%5Cfrac%7B1%7D%7B%28x%2Ba%29%28%5Csqrt%7Bx-b%7D%2B%5Csqrt%7Ba-b%7D%29%7D%3D%5Cfrac%7B1%7D%7B4a%5Csqrt%7Ba-b%7D%7D%24)
Entonces calculemos el límite
______________________________________________________________
Llevamos al límite
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años